The Influence of Transformational Leadership and Employee Agility on Organizational Citizenship Behavior (OCB) and Its Impact on Employee Performance at PT Trubus Mitra Swadaya - Meilinda, Friska Catleya; Kusiyah, Kusiyah; Adha, Shultonnyck (Privietlab, 2025)
This study investigates the influence of transformational leadership and employee agility on Organizational Citizenship Behavior (OCB) and its subsequent impact on employee performance at PT Trubus Mitra Swadaya, Jakarta. Employing a quantitative approach with Structural Equation Modeling (SEM) using SmartPLS 4.0, primary data were collected through questionnaires from 53 respondents. The findings reveal that transformational leadership significantly influences OCB, which in turn has a positive and substantial effect on employee performance. However, employee agility did not significantly affect OCB or performance. Additionally, the study finds that transformational leadership does not directly influence performance, but does so indirectly through OCB, which acts as a full mediator. Conversely, OCB did not mediate the relationship between employee agility and performance. These results underscore the importance of fostering OCB through transformational leadership to enhance employee outcome. This study contributes to the understanding of leadership and behavioral dynamics in post-pandemic organizational settings and offers practical implications for human resource strategies aimed at improving employee performance through value-driven leadership and a supportive organizational culture.